Structural performance enhancement: bio-inspired honeycomb solutions for high-velocity hail impact challenges - Solak, Alparslan (SPRINGER HEIDELBERG, 2024)
This study investigates the mechanical performance of bio-inspired honeycomb sandwich structures under high-speed hail impacts. A detailed Ls-Dyna model was developed and validated using experimental results from hail impact tests on Carall composite structures from the literature, with the model's accuracy confirmed through alignment of post-impact damage patterns, z-axis displacement values, and initial energy absorption with experimental data. Mesh refinement techniques, ranging from coarse to fine elements, were applied, revealing that smaller mesh sizes provided more detailed damage representation and improved accuracy in critical areas. Various impact angles (22.5 degrees, 45 degrees, 67.5 degrees, and 90 degrees) were analyzed to simulate real-world conditions, demonstrating that higher angles, particularly 90 degrees, resulted in the most severe damage. Additionally, eight different honeycomb configurations, including hexagonal and bio-inspired designs, were incorporated into the sandwich structure model. The results showed that hexagonal, re-entrant, wavy, and SI honeycombs sustained substantial damage, while spider web, bamboo, pomelo peel, and grass stem designs exhibited superior resistance. Among all, the wavy honeycomb model achieved the highest specific energy absorption (sEA), showing a 5.62% improvement over the hexagonal model. This research underscores the potential of bio-inspired honeycomb structures in enhancing impact resistance, offering valuable insights for future design strategies in impact-critical applications.
Keywords: Bioinspiration; Hail impact resistance; Honeycomb structures; Ls-Dyna; Finite element analysis; Sandwich structures; Specific energy absorption (sEA); ENERGY-ABSORPTION; RESISTANCE; Engineering